Infrared-active vibron bands associated with rare gas atom dopants isolated in solid parahydrogen: Quantum Crystals - Raston, P.L.; Anderson, D.T. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
We report high-resolution infrared absorption spectroscopic studies of the dopant-induced Q1(0) vibron band in solid parahydrogen crystals doped with low concentrations of rare gas atoms. The frequency, lineshape, and integrated absorption coefficient for the rare gas atom-induced Q1(0) vibron band are measured for Ne, Ar, Kr, and Xe. The observed lineshapes and peak maxima frequencies are sensitive to the H2 vibrational dependence of the dopant-H2 isotropic intermolecular potential. Trends observed for Ar, Kr and Xe indicate the vibrational dependence is strong enough for Xe to trap the infrared-active vibron in its firstsolvation shell while for Ar the vibron remains delocalized. The Ne-induced feature displays a qualitatively different lineshape which is attributed to the weak intramolecular vibrational dependence of the Ne–H2 intermolecular potential relative to the H2–H2 interaction. The lineshapes of the Ar, Kr, and Xe dopant-induced Q1(0) pure vibrational features agree well with recent first principles calculations.